Transformasi Ekosistem Halal: Pendampingan Self Declare Berbasis Komunitas Melalui Klinik Mobile dan Halal Champion - Endah Emiarti; M.Ridho Anasya Romadhoni; Lita Nia Rahmadani; Syifaun Nadhiroh; Mila Minhatul Maula (LP3M IAIFA Kediri, 2025)
Abstract The acceleration of halal certification for Micro and Small Enterprises (MSEs) in Bojonegoro faces significant challenges, primarily due to low digital literacy and administrative barriers. This community service aims to accelerate the self-declare halal certification process through a Community Based Research (CBR) approach. The intervention strategy involves the implementation of a